Human activities and resultant pressures on key European marine habitats: An analysis of mapped resources. (December 2018) - Dailianis, Thanos; Smith, Christopher J.; Papadopoulou, Nadia; Gerovasileiou, Vasilis; Sevastou, Katerina; Bekkby, Trine; Bilan, Meri; Billett, David; Boström, Christoffer; Carreiro-Silva, Marina; Danovaro, Roberto; Fraschetti, Simonetta; et al.
Abstract: Human activities exert a wide range of pressures on marine ecosystems, often resulting in the loss of species and degradation of habitats. If effective policies and management practices to restore past damage and reduce future impacts to the marine environment are to be developed, knowledge of the extent, duration and severity of activities and pressures is essential, yet often lacking. As part of the EU H2020 project "Marine Ecosystem Restoration in Changing European Seas", this study uses an exhaustive review of published records, web resources, and grey literature to comprehensively assess the degree to which human activities and pressures are mapped within European seas. The results highlight a number of limitations and gaps, including: (a) limited geographic coverage at both the regional and sub-regional level; (b) insufficient spatial resolution and accuracy in recorded data for the planning of conservation and restoration actions; (c) a lack of access to the background data and metadata upon which maps are based, thus limiting the potential for synthesis of multiple data sources. Based on the findings, several recommendations for future marine research initiatives arise, most importantly the need for coordinated, geographically extended baseline assessments of the distribution and intensity of human activities and pressures, complying with high-level standardization regarding methodological approaches and the treatment of produced data. Highlights: Mapping of marine activities and pressures is essential for conservation and policy. A review was performed to assess existing map sources for European waters. Gaps and inconsistencies were identified regarding spatial coverage and resolution. Lack of standardization and availability restricts usefulness of mapped data. Coordinated and standardized approaches are required for future initiatives.